MAQĀṢID AL-SYARĪ’AH DALAM TINJAUAN PEMIKIRAN IBNU ‘ĀSYŪR - Muchasan, Ali; Syarif, M.; Rohmawan, Dhuhaa (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2023)
Maqāṣid Al-Syarī'ah from the perspective of Ibnu 'Āsyūr, a contemporary scholar who has contributed greatly to developing maqasidus sharia, not only from the point of view of how Islamic law becomes a means for individuals to get closer to God, but also how humans actually function as individual beings , social beings and Godly beings. Understanding and developing Maqasidus sharia knowledge becomes tenting for us to be able to feel the spirit of tasyri' so that our faith will increase. Maqasid al Sharia can be in the form of maqasid al'ammah sharia, which covers all aspects of sharia and Maqāṣid Al-Syarī'ah al khasah which is devoted to one of the chapters of sharia that has chapters, such as maqasid al sharia in economics, family law and others , or Maqāṣid Al-Syarī'ah al juz'iyyah which includes every syara' law such as the obligation to pray, forbidden adultery, and so on. In this paper, the discussion will be focused on the maqashid sharia theory according to Ibn 'Āsyūr. With the hope of knowing the characteristics and uniqueness of the theory. This research is a research that uses a qualitative descriptive approach using the literature study method, namely by searching for and studying literature related to the problem that is the object of this research study. Ibn 'Āsyur on maqashid al syar'iyyah.